Development of a convenient and rapid screening zebrafish model to investigate lethal effects and immunocompromised states of uremic toxins - Pema Jo; Rui Zhang; Yuhua Zhang; Zhilian Li; Yanhua Wu; Shuqiong Zhang; Tsring Lhamo; Yuanhan Chen (Renal Failure)
Background Uremia is characterized by high mortality and immune dysfunction owing to the accumulation of uremic toxins. Traditional rodent models are complex and time consuming. This study aimed to develop a simple and rapid zebrafish model for investigating the toxicological effects of uremic toxins.Methods Uremic solutions containing small (SUT) and medium-to-large (MLUT) uremic toxins were prepared using waste solution of peritoneal dialysis by a dialysis method. Wild-type zebrafish larvae were used to assess mortality, whereas transgenic (TG) (zlyz:EGFP) zebrafish, with macrophages labeled with green fluorescent protein, were used to evaluate immune status through macrophage migration assays.Results The mortality rates were significantly higher in the SUT- and MLUT-treated groups than in the controls, with SUT showing the strongest lethal effect. Macrophage migration was significantly inhibited in both SUT- and MLUT-treated groups, indicating an immunocompromise. This model effectively mimicked the lethal and immunosuppressive effects of uremia.Conclusion This zebrafish model provides a simple and rapid platform for studying the toxicological effects of uremic toxins and evaluating potential therapeutic interventions.